Un análisis de coyuntura de la situación fiscal colombiana (2017)
The present document analyzes the effects derived from the fiscal deficit in Colombia. The impacts in the national debt, and the establishment of a fiscal restrictive politics(policy) accompanied of tributary(tax) reforms they are some of the determinant factors that go in opposition to financial stability of the country. In view of this panorama, it emerges the competitiveness in the frame of the professionalization and the education as an alternative instrument of fiscal policy that contributes significantly to the performance of the country as for productivity.